EL Salvador : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The primary objective of the program was to prevent a crisis of confidence by signaling policy continuity and providing a liquidity buffer in case such shocks materialized. In addition, the program sought to preserve macroeconomic stability by focusing on sustaining fiscal prudence and financial sector reforms. IMF policy requires an ex post evaluation (EPE) of GRA-supported programs with exceptional access within a year after the end of the arrangement. Large provision of liquidity and effective use of IMF's lending facilities can be effective in preventing a crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet